Vincristine-Induced Seizure Potentiated by Itraconazole Following RCHOP Chemotherapy for Diffuse Large B-Cell Lymphoma - Foroughinia, Farzaneh; Baniasadi, Shadi; Seifi, Sharareh; Fahimi, Fanak (Current Drug Safety, 2012)
Objectives: To report the case of a patient with diffuse large B-cell lymphoma (DLBCL) who developed vincristine (VCR)-induced seizure after R-CHOP chemotherapy. Case Summary: A 22-year-old boy with DLBCL developed generalized tonic clonic seizures following R-CHOP chemotherapy. After receiving the third cycle of chemotherapy, he developed Aspergillus pneumonia; therefore, itraconazole was started 18 days before the administration of cycle 4 of chemotherapy. Seven days after the administration of the fifth doses of vincristine, the patient reported symptoms of gastrointestinal toxicity (abdominal cramps and constipation). Subsequently, he developed three episodes of generalized tonic-clonic seizure which lasted for 2-3 minutes during one day and became unconsciousness. His serum electrolytes were normal with the exception of low serum sodium (128mEq/L). Blood glucose, blood urea nitrogen, the complete blood count, and a cerebrospinal fluid study were also normal. A computed tomography scan of the brain did not show any abnormalities. He had no previous history of convulsion. Occurrence of seizure due to central nervous system invasion of DLBCL was ruled out with a normal cerebrospinal fluid examination, computed tomography scan, and magnetic resonance imaging of the head. Therefore, the patient's neurotoxicity has been attributed to vincristine, the effects of which were likely potentiated by itraconazole therapy. Discussion: Vincristine is a naturally occurring vinca alkaloid used in various chemotherapy regimens. Neurotoxicity is a known and commonly encountered side effect of vincristine. Peripheral neuropathy is the most common form of vincristine neuropathy whereas central effects are rarer. Enhanced VCR neurotoxicities from drug interactions with several azole antifungals such as itraconazole and voriconazole have been reported. Our case represents a drug possible adverse drug effect based on the Naranjo ADR Probability Scale. Conclusion: Administration of vincristine in conjunction with azole antifungals should be with caution and after carefully considering the risks and benefits. Also, it is important to rule out other causes of seizure in these patients.
Keywords: Neurotoxicity